Articular cartilage surface roughness as an imaging‐based morphological indicator of osteoarthritis: A preliminary investigation of osteoarthritis initiative subjects. Issue 12 (23rd May 2017) - Newton, Michael D.; Osborne, Jeffrey; Gawronski, Karissa; Baker, Kevin C.; Maerz, Tristan
ABSTRACT: Current imaging‐based morphometric indicators of osteoarthritis (OA) using whole‐compartment mean cartilage thickness (MCT) and volume changes can be insensitive to mild degenerative changes of articular cartilage (AC) due to areas of adjacent thickening and thinning. The purpose of this preliminary study was to evaluate cartilage thickness‐based surface roughness as a morphometric indicator of OA. 3D magnetic resonance imaging (MRI) datasets were collected from osteoarthritis initiative (OAI) subjects with Kellgren–Lawrence (KL) OA grades of 0, 2, and 4 ( n  = 10/group). Femoral and tibial AC volumes were converted to two‐dimensional thickness maps, and MCT, arithmetic surface roughness (Sa ), and anatomically normalized Sa (normSa ) were calculated. Thickness maps enabled visualization of degenerative changes with increasing KL grade, including adjacent thinning and thickening on the femoral condyles. No significant differences were observed in MCT between KL grades. Sa was significantly higher in KL4 compared to KL0 and KL2 in the whole femur (KL0: 0.55 ± 0.10 mm, KL2: 0.53 ± 0.09 mm, KL4: 0.79 ± 0.18 mm), medial femoral condyle (KL0: 0.42 ± 0.07 mm, KL2: 0.48 ± 0.07 mm, KL4: 0.76 ± 0.22 mm), and medial tibial plateau (KL0: 0.42 ± 0.07 mm, KL2: 0.43 ± 0.09 mm, KL4: 0.68 ± 0.27 mm). normSa was significantly higher in KL4 compared to KL0 and KL2 in the whole femur (KL0: 0.22 ± 0.02, KL2: 0.22 ± 0.02, KL4: 0.30 ± 0.03), medial condyle (KL0: 0.17 ± 0.02, KL2: 0.20 ± 0.03, KL4: 0.29 ± 0.06), whole tibia (KL0: 0.34 ± 0.04, KL2: 0.33 ± 0.05, KL4: 0.48 ± 0.11) and medial plateau (KL0: 0.23 ± 0.03, KL2: 0.24 ± 0.04, KL4: 0.40 ± 0.10), and significantly higher in KL2 compared to KL0 in the medial femoral condyle. Surface roughness metrics were sensitive to degenerative morphologic changes, and may be useful in OA characterization and early diagnosis. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2755–2764, 2017. Abstract : A custom algorithm was used to create two‐dimensional articular cartilage thickness maps of patients from the Osteoarthritis Initiative. Thickness maps demonstrate significantly increased surface roughness as a function of increasing Kellgren–Lawrence (KL) osteoarthritis (OA) grade, particularly in the medial femoral condyle, though mean cartilage thickness was not found to differ significantly between KL grades. Surface roughness‐based metrics have potential utility as morphological indicators of OA.